GROWTH OF Schizolobium parahyba UNDER BIOSOLIDS and MINERAL FERTILIZER APPLICATION - Silva, Eduardo Vinícius da; Rocha, Nathália Felipe da; Medeiros das Chagas Silva, Oclizio; Júnior, José Carlos Arthur; Araujo, Emanuel José Gomes de; Leles, Paulo Sérgio dos Santos (Floresta, 2025)
The objective of this study was to evaluate the growth of Schizolobium parahyba under application of biosolids and mineral fertilizers. Seedlings of the species were planted in 18 L pots following an experimental design in 5 randomized blocks with two types of soils: sandy and clayey. The treatments were: B0F100 (mineral fertilizers only), B25F75 (2 L of biosolids + mineral fertilizers), B50F50 (4 L of biosolids + mineral fertilizers), B75F25 (6 L of biosolids + mineral fertilizers), B100F0 (8 L of biosolids), and B0F0 (control). At 113 days after transplantation, seedling height and root collar diameter were measured using a measuring tape and a caliper, respectively. Then the plants were cut and the leaf area was measured using LI-COR (LI-3100C). Subsequently, they were placed in an oven at 65 °C and then weighed on a precision scale to assess their aerial and root dry matter. The best responses in the variables analyzed in the clayey soil were achieved mainly with the exclusive application of biosolids, despite the fact that this soil presented lower fertility than the sandy soil. As for the sandy soil, the highest growth of S. parahyba was achieved with balanced amounts of biosolid and mineral fertilizers; the B75F25 treatment in particular showed the best results. The biosolid positively influenced the growth of S. parahyba both in clayey and sandy soil. Biosolid is therefore an important alternative to be considered as a source of nutrients in forest plantations.